1992
DOI: 10.1073/pnas.89.15.7105
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of DNA adduct formation in HL-60 cells by combinations of benzene metabolites.

Abstract: Using P1 nuclease enhanced 32p postlabeling, we investigated DNA adduct formation in HL-60 promyelocytic leukemia cells treated with the benzene metabolites hydroquinone, catechol, and 1,2,4-benzenetriol. Comparison of the slopes of the dose-response curves showed that hydroquinone was 7-9 times more effective than 1,2,4,-benzenetriol and catechol at inducing DNA adducts. Comparison of hydroquinone with catechol showed a good correlation between adduct formation and cytotoxicity. Similar comparisons of hydroqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 33 publications
1
38
0
1
Order By: Relevance
“…[31][32][33][34][35] In particular, growing evidence suggests that metabolites derived from hydroquinone, including 1,2,4-benzenetriol and particularly 1,4-benzoquinone, [36][37][38] are highly toxic. [10][11][12][13] However, other studies have shown synergistic eVects between combinations of hydroquinone and other metabolites including phenol and catechol. [39][40][41] Thus, although the latest evidence points to hydroquinone having a central role in benzene toxicity, a role for other metabolites cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34][35] In particular, growing evidence suggests that metabolites derived from hydroquinone, including 1,2,4-benzenetriol and particularly 1,4-benzoquinone, [36][37][38] are highly toxic. [10][11][12][13] However, other studies have shown synergistic eVects between combinations of hydroquinone and other metabolites including phenol and catechol. [39][40][41] Thus, although the latest evidence points to hydroquinone having a central role in benzene toxicity, a role for other metabolites cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…26,28,29 Further, combinations of the phenolic metabolites of benzene enhance DNA adduct formation. 30,31 It has therefore been suggested that all the phenolic metabolites of benzene play a role in benzene-induced toxicity, and that it is the combination that is most toxic. 24,32 Phenol and hydroquinone produce genetic damage of the type found in leukemia Quinones derived from phenol, catechol, hydroquinone and 1,2,4-benzenetriol cause various forms of genetic damage Leukemia including chromosome breakage and aneuploidy.…”
Section: Figurementioning
confidence: 99%
“…Pongracz et al (30,31) and Levay et al (32) subsequently combined these spectroscopic methods of structural analysis with the sen- (36) and that peroxidase activation of hydroquinone is required for adduct formation (37), no attempts were made to link adduct formation with any end point of toxicity other than cytotoxicity. We recently evaluated the significance of DNA adduct formation in toxicity by studying the effects of benzene metabolites on DNA adduct formation and retinoic acid-induced granulocytic differentiation in this model (38).…”
Section: Microsomal Metabolismmentioning
confidence: 99%